Design considerations of variable rate liquid fertilizer applicator for mature oil palm trees - Yamin, Muhammad; Wan Ismail, Wan Ishak; Abd Aziz, Samsuzana; Mohd Kassim, Muhamad Saufi; Akbar, Farah Naz; Ibrahim, Muhammad (Springer, 2022)
This research study focuses on the design of variable rate liquid fertilizer applicator which can measure the NPK status of soil and applies N, P and K nutrients simultaneously at separate variable rates around the oil palm trees in the form of aqueous solutions of straight fertilizers having single nutrient. A fertilizer flow control and spray system was designed to apply liquid fertilizer around the oil palm tree on a 5 m × 5 m (25 m2) area of most effective roots. On the basis of simulation and calculations, six 8006 flat fan nozzles were selected to maintain the adequate swath coverage of fertilizer spray. The nozzles 1–3 were mounted vertically on the horizontal boom to spray on the machine side of an oil palm tree, i.e. the side of an oil palm where the machine is passing through. Whereas nozzles 4–6 were fixed at − 22°, − 21° and − 20° angles with respect to the horizontal plane on a 45° angled boom to spray across the tree using trajectory method. An average simulated liquid velocity of 14.05 m/s from each nozzle was found to spray at 2.5 m distance across the tree using trajectory method. Thus an improved distribution of fertilizer around the tree at 25 m2 area of most effective roots can be achieved using this system. Mechanical structure of the applicator which carries all the equipment and fertilizer tanks was designed by using the finite element analysis. Minimum safety factors of 3.13 and 11.34 were found for mechanical structure and fertilizer tank assembly respectively which were satisfactory to bear the necessary loads during field operation.